Pemeriksaan mikroskopis keluhan kulit pada santri Pesantren Khazanah Kebajikan kota Palembang - Ahmad Ghiffari; Indri Ramayanti; Reza Al Fath; Putri Rizki Amaliah Badri (Fakultas Kedokteran Universitas Sriwijaya, 2020)
The prevalence of skin diseases such as scabies, dermatitis and pedikulosis capitis in boarding school is high and often overlooked. Skin disease can be caused by many pathogens therefore particular treatment can be effective if followed by additional a microscopic examination. Correct examination of microscopic test can provide necessary information regarding the knowledge to prevent certain skin diseases. This social activities aimed at providing proper knowledge through exact diagnose of skin disease. The benefit of using such microscopictest is to select the correct practice regarding the transmission of disease causing the morbidity of skin diseases in Ponpes Khazanah Kebajikan. Steps or the activities were the provision of a questionnaire, clinical examination, and microscopic examination followed by treatment. Results obtained 48 of 59 female students infestated with pediculosis, and 46 positive male students suffer with dermatofitosis. Such activities of microscopic examination of skin disease in Pesantren should be continue and to proceed with appropriate prevention activities. Counseling about the dangers of skin disease transmission by scabies, pediculosis and dermatofitasis needed to be educate and practice by the students whether one who already suffered nor yet.